Lemongrass (Cymbopogon citratus DC. Stapf) essential oil microparticles: Development, characterization, and antioxidant potential - Martins, Wanderson da Silva (2021)
Maltodextrin (DE 20) and gelatin (4:1, w/w, respectively) were investigated as encapsulant materials for lemongrass (Cymbopogon citratus DC. Stapf) essential oil microencapsulation by freeze-drying. Three formulations were prepared: M1 (5% essential oil), M2 (10% essential oil), and M3 (15% essential oil), all in w/w. Microparticles were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, water activity measurement, thermogravimetric and derivative thermogravimetric analysis, differential scanning calorimetry, and antioxidant activity analysis. Yield and microencapsulation efficiency were also determined. The results showed the promising potential of maltodextrin and gelatin as encapsulants and confirmed the feasibility of preparing C. citratus essential oil microparticles by freeze-drying. Microencapsulation improved the oil?s thermal and oxidative stability, providing protection from volatilization and environmental conditions. Scanning electron microscopic examination of M1 revealed a closed, pore-free surface. M1 had higher yield and microencapsulation efficiency, showing great commercial potential for its reduced storage, transport, and distribution costs.